2011
DOI: 10.1080/15295192.2011.613726
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Control in Contexts of Political Violence: Testing Bidirectional Relations Between Violence Exposure and Control in Post-Accord Belfast

Abstract: SYNOPSIS Objective The goal of the present study is to examine bi-directional relations between youth exposure to sectarian and nonsectarian antisocial behavior and mothers’ efforts to control youth’s exposure to community violence in Belfast, Northern Ireland. Design Mother-child dyads (N=773) were interviewed in their homes twice over 2 years regarding youth’s exposure to sectarian (SAB) and nonsectarian (NAB) community antisocial behavior and mothers’ use of control strategies, including behavioral and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Thus, it is imperative for researchers to avoid collapsing the various dynamics associated with violence into a singular, static notion and to diligently consider those dynamics in studies with youth as best we can (Daiute, 2006; Townsend et al, 2020). To this end, some scholars have now examined varying youth developmental outcomes associated with different types of exposure to community‐level violence (i.e., political and nonpolitical) (Dubow et al, 2009; Merrilees et al, 2011). Studies on children's and adolescents' moral development would also benefit from differentiating between different types of violence occurring at the community level, involving different community members, in understanding how youth evaluate and make sense of the violence impacting their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is imperative for researchers to avoid collapsing the various dynamics associated with violence into a singular, static notion and to diligently consider those dynamics in studies with youth as best we can (Daiute, 2006; Townsend et al, 2020). To this end, some scholars have now examined varying youth developmental outcomes associated with different types of exposure to community‐level violence (i.e., political and nonpolitical) (Dubow et al, 2009; Merrilees et al, 2011). Studies on children's and adolescents' moral development would also benefit from differentiating between different types of violence occurring at the community level, involving different community members, in understanding how youth evaluate and make sense of the violence impacting their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, mother–child correspondence for autonomy support has been moderate at best, with correlations that ranged from small (.14; Grolnick, Ryan, & Deci, 1991) to moderate (.36; Brenning, Soenens, Braet, & Bal, 2012), whereas for involvement, it ranged from no relation ( r = .03; Sessa, Avenevoli, Steinberg, & Morris, 2001) to a strong one (.50; Rohner et al, 2005). For structure, mother–child correspondence ranged from nil ( r = .04; Logsdon et al, 2013) to high ( r = .61; Merrilees et al, 2011). Hence, including mothers’ perspective in future research will allow identifying the extent to which their self-reported need-supporting behaviors explain additional variance in their children’s psychological need satisfaction and adjustment in school in a possibly nonredundant way.…”
Section: Discussionmentioning
confidence: 99%
“…Through this wider social network, mothers may feel more capable of monitoring children's behavior to protect them from nonsectarian antisocial behavior within the community. A two‐wave study found that child exposure to nonsectarian, but not sectarian, antisocial behavior predicted maternal behavioral control, such as needing parental permission to go out with friends (Merrilees et al., 2011). This adaptive parenting strategy suggests that mothers may feel more efficacious in protecting their children in the face of nonsectarian violence, which in turn may buffer them from greater mental health problems.…”
Section: Discussionmentioning
confidence: 99%